Effects of problem-based learning approach on cognitive variables of university students - Bayat, Sahar; Ahmad Tarmizi, Rohani (Elsevier, 2012)
This study aimed to investigate the effectiveness of PBL approach on cognitive variables among postgraduate students who were taking Educational Statistic course. Two groups of students namely; PBL group and conventional instruction (CI) group were investigated on overall performance, conceptual knowledge, procedural knowledge, mental load, number of errors and instructional efficiency. Comparison of overall performance and procedural knowledge of PBL and CI group’ students indicated a significant difference between these two groups (t[46]= -2.143, p<0.05), (t [46]= -2.091, p<0.05). In addition, there is significant difference between these two groups on mental load during learning process (t [46] = -3.283, p<0.05).